Fabrication and characterization of PU/NKLNT/CFs based lead-free piezoelectric composite for energy harvesting application. Issue 12 (13th August 2021) - Chelli, Zakia; Achour, Hakim; Saidi, Malika; Laghrouche, Mourad; Chaouchi, Ahcene; Rguiti, Mohamed; Lorgouilloux, Yannick; Courtois, Christian.
ABSTRACT: For vibration energy harvesting applications, a flexible composite material based on a polyurethane (PU) polymer matrix filled with polycrystalline particles (Na0.535K0.48)0.966 Li0.058 Nb0.9Ta0.1O3 (NKLNT) and crushed carbon fibers (CFs) has been developed by tape-casting method. NKLNT was synthesized by the solid-state route. The powder mixture of NKLNT and CFs was dispersed in the solution obtained by dissolving polyurethane in Cyclohexane. A maximum electrical power has been obtained for 0.5 wt.% at an electrical resistance of 5.10 5 Ω, which allows us to supply low-power electronic systems. A high piezoelectric charge coefficient (d33 = 147pC.N −1 ) of NKLNT indicates its potential application in flexible energy harvesting. Graphical Abstract: uf0001